The role of exosomal non‐coding RNAs in aging‐related diseases. (23rd February 2021) - Dolati, Sanam; Shakouri, Seyed Kazem; Dolatkhah, Neda; Yousefi, Mehdi; Jadidi‐ Niaragh, Farhad; Sanaie, Sarvin
Abstract: Aging is a biological process caused by the accumulation of senescent cells with a permanent proliferative arrest. To the influence of aging on human life expectancy, there is essential for new biomarkers which possibly will assistance in recognizing age‐associated pathologies. Exosomes, which are cell‐secreted nanovesicles, make available a new biomarker detection and therapeutic approach for the transfer of different molecules with high capacity. Recently, non‐coding RNAs (ncRNA) which are contained in exosomes have developed as important molecules regulating the complexity of aging and relevant human diseases. The discovery of ncRNA provided perceptions into an innovative regulatory platform that could interfere with cellular senescence. The non‐coding transcriptome includes a different of RNA species, spanning from short ncRNAs (<200 nucleotides) to long ncRNAs, that are >200 bp long. Upgraded evidence displays that targeting ncRNAs possibly will influence senescence pathways. In this article, we will address ncRNAs that participated in age‐related and cellular senescence diseases. Growing conception of ncRNAs in the aging process possibly will be responsible for new understandings into the improvement of age‐related diseases and elongated life span.